Lightweight high-strength magnesium oxysulfate composite fireproof plate and preparation method thereof

CN122919099APending Publication Date: 2026-10-16CHANGZHOU BULU SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147286.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明解决的技术问题在于现有硫氧镁防火板在降低密度的同时难以兼顾高强度,且板材内部游离水分脱除不彻底导致容易发生泛霜及尺寸变形

Benefits of technology

[0070]1、本发明通过致密底层、轻质芯层与致密面层交替叠加结构,并在对应层间设置三层玻纤网格布,形成协同受力体系。致密底层和致密面层提供板材表面硬度与抗折强度。轻质芯层内部引入蛋白质发泡剂泡沫产生闭孔,结合膨胀珍珠岩与空心玻璃微珠的物理轻质特性,降低复合防火板总体积密度,阻断热量传递路径,实现轻量化与防火隔热性能的兼顾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122919099A_ABST
    Figure CN122919099A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of building fireproof plate, and discloses a light high-strength magnesium oxysulfate composite fireproof plate and a preparation method thereof, which comprises, from bottom to top, a first layer of glass fiber mesh cloth, a dense bottom layer, a second layer of glass fiber mesh cloth, a light core layer, a third layer of glass fiber mesh cloth and a dense surface layer, wherein the dense bottom layer and the dense surface layer are formed by curing of dense layer slurry, and the light core layer is formed by curing of light core layer slurry, and the light core layer slurry is made by mixing matrix slurry and protein foaming agent foam, and the preparation method comprises pouring the slurry layer by layer and laying the glass fiber mesh cloth to obtain a preliminary formed composite plate; the preliminary formed composite plate is placed in a vacuum suction filter device for negative pressure dewatering treatment to discharge excess free water, and the finished product is obtained after demolding and curing. Through the setting of the laminated structure and the cooperation of the vacuum negative pressure dewatering process, the light weight and high strength are realized, and the problems of halogen return and size deformation caused by water are eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fireproof building materials technology, specifically to a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board and its preparation method. Background Technology

[0002] Magnesium oxysulfate fireproof boards, as inorganic non-combustible boards, are widely used in building partitions and ceilings. To reduce building weight and improve construction convenience, conventional techniques typically add lightweight physical fillers or foaming agents to the mortar to lower the board's density. Introducing a porous structure and lightweight aggregates into the mortar weakens the board's load-bearing framework, leading to a decrease in the board's flexural strength and impact resistance. Existing single-layer homogeneous molding processes cannot simultaneously achieve both lightweighting and mechanical strength.

[0003] Existing magnesium oxysulfate fireproof boards have a potential problem with residual moisture during the natural curing stage. During the later stages of curing, as free moisture evaporates naturally, it forms interconnected capillary pores within the board, reducing the matrix density. This free water dissolves unreacted soluble salts within the board, and as the moisture migrates to the surface, it precipitates, causing blooming and efflorescence. The volumetric shrinkage stress accompanying moisture loss can easily lead to macroscopic dimensional deformation of the board. Furthermore, the hydrated crystal network generated in the existing formulation lacks sufficient toughness; when subjected to changes in external temperature and humidity or internal shrinkage stress, micro-cracks easily form at the crystal phase interfaces and propagate outwards, causing overall cracking of the board. Summary of the Invention

[0004] The technical problem solved by this invention is that existing magnesium oxysulfate fireproof boards are difficult to maintain high strength while reducing density, and the incomplete removal of free moisture inside the board makes it prone to frost and dimensional deformation.

[0005] To address the above problems, the present invention provides the following technical solution:

[0006] In a first aspect, the present invention provides a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board, employing the following technical solution:

[0007] A lightweight, high-strength magnesium sulfate-oxygen composite fireproof board includes a first layer of fiberglass mesh, a dense bottom layer, a second layer of fiberglass mesh, a lightweight core layer, a third layer of fiberglass mesh, and a dense top layer, which are stacked sequentially from bottom to top; the dense bottom layer and the dense top layer are formed by curing a dense layer slurry, and the lightweight core layer is formed by curing a lightweight core layer slurry;

[0008] The dense layer slurry is made from raw materials comprising the following parts by weight:

[0009] Lightly calcined magnesium oxide: 100 parts;

[0010] Magnesium sulfate heptahydrate: 45-65 parts;

[0011] Water: 50-70 parts;

[0012] Wollastonite powder: 20-50 parts;

[0013] Latex powder: 5-12 parts;

[0014] Pigment: 1-5 parts;

[0015] Polypropylene fiber: 0.3-0.8 parts;

[0016] Magnesium sulfide modifier: 1-3 parts;

[0017] The lightweight core layer slurry is made by mixing the matrix slurry with protein foaming agent, and 3-10 parts by volume of protein foaming agent are added to the matrix slurry.

[0018] The matrix slurry is made from raw materials comprising the following parts by weight:

[0019] Lightly calcined magnesium oxide: 100 parts;

[0020] Magnesium sulfate heptahydrate: 50-80 parts;

[0021] Water: 60-90 parts;

[0022] Plant fiber: 15-40 parts;

[0023] Expanded perlite: 10-30 parts;

[0024] Hollow glass microspheres: 5-15 parts;

[0025] Polypropylene fiber: 0.1-0.4 parts;

[0026] Magnesium sulfide modifier: 1.5-3.5 parts.

[0027] By adopting the above technical solution, a sandwich-like layered structure consisting of a dense bottom layer, a lightweight core layer, and a dense surface layer, combined with three layers of fiberglass mesh, is formed to create a mechanically synergistic stress-bearing system. The dense surface layer provides surface hardness and impact resistance, while the core layer achieves lightweighting, thermal insulation, and flame retardancy.

[0028] Lightly calcined magnesium oxide and magnesium sulfate heptahydrate undergo a hydration reaction in water to form a needle-like crystalline network with a phase composition of 5Mg(OH)2·MgSO4·7H2O, which constitutes the high-strength load-bearing skeleton of the board.

[0029] In the lightweight core layer, the protein foaming agent creates independent closed cells. Combined with the physical lightweight properties of expanded perlite and hollow glass microspheres, it significantly reduces the overall bulk density of the board while blocking the heat transfer path and improving fire resistance and heat insulation performance.

[0030] In the dense layer, wollastonite powder fills the micropores of hydration products, and after the latex powder forms a film, it creates flexible connections between inorganic crystals, improving the toughness of the board and preventing cracking. The addition of magnesium oxysulfate modifier inhibits the formation of byproducts and promotes the hydration reaction towards the formation of a high-strength, stable phase. Polypropylene fibers form a three-dimensional random distribution in the slurry, playing a microscopic role in preventing and inhibiting cracking.

[0031] Preferably, the length of the polypropylene fibers in the dense layer slurry is 6 mm; the length of the polypropylene fibers in the matrix slurry is 3 mm.

[0032] By adopting the above technical solution, polypropylene fibers of different lengths are matched to the stress characteristics of different layers. 6mm fibers resist macroscopic shrinkage stress in the dense layer, while 3mm fibers adapt to the porous structure in the lightweight core layer, preventing microscopic cracking of the pore walls.

[0033] Preferably, the thickness of both the dense bottom layer and the dense top layer is 2-4 mm; the thickness of the lightweight core layer accounts for 60%-75% of the total thickness of the lightweight high-strength sulfur-oxygen magnesium composite fireproof board.

[0034] By adopting the above technical solutions, the thickness ratio distribution can maximize the overall lightweighting while ensuring that the overall flexural strength and surface hardness of the board do not decrease.

[0035] Preferably, the wollastonite powder has a fineness of 800 mesh; the latex powder is a redispersible latex powder; and the true density of the hollow glass microspheres is 0.15-0.25 g / cm³. 3 The plant fiber is wood powder or bamboo powder with a fineness of 80-120 mesh; the expanded perlite has a particle size of 0.5-1.5 mm.

[0036] By adopting the above technical solutions, the needle-like crystal morphology of calcium metasilicate and the hydration products of magnesium oxysulfate intertwine to enhance structural stability; the vinyl acetate-ethylene copolymer redispersible latex powder has excellent water resistance and film-forming properties, improving interfacial adhesion; the borosilicate material is resistant to high temperatures, maintains the integrity of the microsphere structure under fire conditions, and enhances fire resistance.

[0037] Secondly, the present invention provides a method for preparing a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board, employing the following technical solution:

[0038] A method for preparing a lightweight, high-strength magnesium oxysulfate composite fireproof board includes the following steps:

[0039] A first layer of fiberglass mesh is laid at the bottom of the molding mold. A dense layer of slurry is poured onto the surface of the first layer of fiberglass mesh, the dense layer of slurry is smoothed, and it is left to stand until it initially sets to obtain a dense bottom layer.

[0040] A second layer of fiberglass mesh is laid on the surface of the dense base layer. Lightweight core layer slurry is poured onto the surface of the second layer of fiberglass mesh. The lightweight core layer slurry is smoothed and left to stand until initial setting to obtain the lightweight core layer.

[0041] A third layer of fiberglass mesh is laid on the surface of the lightweight core layer, and a dense layer slurry is poured on the surface of the third layer of fiberglass mesh. The dense layer slurry is then smoothed to obtain a dense surface layer, which in turn yields a preliminary composite board.

[0042] The pre-formed composite board, along with the forming mold, is placed in a vacuum suction filter device for negative pressure dehydration treatment to remove free water and obtain a dehydrated composite board.

[0043] Demolding of the dehydrated composite board, sending the dehydrated composite board into the pre-curing room for curing, and then transferring it to the room temperature curing area for curing to obtain the cured composite board.

[0044] The surface of the curing composite board is sanded to a fixed thickness, the surface of the curing composite board is cleaned, and UV paint or decorative surface is applied to the surface of the curing composite board to obtain a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board.

[0045] By adopting the above technical solution, a molding process combining layer-by-layer pouring and static initial setting is used to ensure that adjacent layers are in contact during the initial setting state, thus ensuring a strong bond at the chemical cross-linking interface between layers and preventing delamination and peeling after curing.

[0046] Setting up a vacuum negative pressure dehydration process is a core step in improving the durability of the boards and preventing deformation. The specific mechanism involves the following steps:

[0047] The first step involves using vacuum negative pressure to generate directional suction force, which forces the material to penetrate the internal pores of the pre-formed composite board and extract excess free water that did not participate in the initial hydration reaction.

[0048] The second step, after the free water is drained, blocks the path of capillary pore formation caused by the natural evaporation of water in the later stage, reduces the overall porosity of the board, and improves the density of the matrix.

[0049] The third step, removing excess moisture, can completely eliminate the driving force for soluble salts to migrate and precipitate to the surface of the board with the moisture, thus preventing frost and efflorescence from the root.

[0050] The combination of pre-curing and room temperature curing ensures that the hydration and crystallization reaction proceeds fully under suitable temperature and humidity conditions, avoiding shrinkage, cracking, and deformation caused by rapid water loss.

[0051] Preferably, the dense layer slurry is prepared in advance through the following steps:

[0052] Add the prescribed amounts of lightly calcined magnesium oxide, magnesium sulfate heptahydrate, and water to a mixer and stir at low speed for 3-5 minutes to obtain the first mixture.

[0053] Add the formulated amounts of wollastonite powder, latex powder, and pigment to the first mixture and stir at medium speed for 5-8 minutes to obtain the second mixture.

[0054] Add the prescribed amount of polypropylene fiber and magnesium oxysulfate modifier to the second mixture and stir at high speed for 3 minutes to obtain a dense slurry.

[0055] By adopting the above technical solution, a step-by-step mixing process of low-speed mixing of powder and liquid, medium-speed dispersion of filler and adhesive powder, and high-speed dispersion of fiber and modifier is used to prevent powder agglomeration and ensure that trace components are uniformly dispersed in the slurry system.

[0056] Preferably, the lightweight core layer slurry is prepared in advance through the following steps:

[0057] Dilute the protein foaming agent with water 30-50 times, and then use a foaming machine to foam the diluted protein foaming agent to obtain protein foaming agent foam.

[0058] Add the formulated amounts of lightly calcined magnesium oxide, magnesium sulfate heptahydrate, water, and magnesium sulfate modifier to a mixer and stir at low speed for 3 minutes to obtain the third mixture.

[0059] Add the plant fiber, expanded perlite, hollow glass microspheres and polypropylene fiber in the formula to the third mixture and stir at medium speed for 5 minutes to obtain the matrix slurry.

[0060] Add the protein foaming agent of the specified volume to the base slurry and stir slowly at 40-60 rpm for 2-3 minutes to obtain a lightweight core layer slurry.

[0061] By adopting the above technical solution, the foaming agent foam is prepared separately and added to the matrix slurry in the final stage. Combined with slow stirring, the high shear force of the stirring blades is avoided from damaging the foam liquid film, ensuring that a uniform and stable closed-cell structure is formed inside the lightweight core layer.

[0062] Preferably, the vacuum degree of the negative pressure dehydration treatment is -0.06MPa to -0.08MPa, and the dehydration time is 3-5 minutes; after the free water is discharged, the moisture content of the initially formed composite board is reduced to 40%-50%.

[0063] By adopting the above technical solution, controlling the negative pressure parameters can effectively extract free water without damaging the air bubbles and hollow microspheres in the lightweight core layer.

[0064] Limit the final dehydration moisture content and retain an appropriate amount of moisture for the subsequent curing and solidification stages to continue the hydration reaction and prevent premature water shortage from causing the reaction to stagnate.

[0065] Preferably, the temperature of the pre-curing chamber is 30-40℃, the humidity is greater than or equal to 90%, and the curing time is 24 hours; the temperature of the normal temperature curing area is 20-30℃, and the curing time is 14 days.

[0066] By adopting the above technical solution, the high temperature and high humidity pre-curing conditions promote the rapid nucleation and growth of the 5Mg(OH)2·MgSO4·7H2O crystal phase, forming initial structural strength; long-term room temperature curing allows the internal stress of the crystal structure to be fully released, the phase transformation to be completely completed, and the cured product to reach the final stable state.

[0067] Preferably, the time for leveling the dense slurry layer and allowing it to stand until initial setting is 15-20 minutes; the time for leveling the lightweight core slurry layer and allowing it to stand until initial setting is 30-40 minutes; and the thickness tolerance of the fixed-thickness sanding is controlled at ±0.3mm.

[0068] By employing the above technical solution, the initial setting times of the two types of slurry are precisely matched. The dense layer sets faster, quickly forming a supporting surface; the lightweight core layer sets slower, which is conducive to the stable distribution of internal air bubbles. Thickness tolerance control ensures the physical dimensional flatness of the final board, meeting the requirements for architectural decorative veneers.

[0069] This invention provides a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board and its preparation method. It has the following beneficial effects:

[0070] 1. This invention employs an alternating superimposed structure of a dense bottom layer, a lightweight core layer, and a dense top layer, with three layers of fiberglass mesh fabric placed between corresponding layers to form a synergistic stress-bearing system. The dense bottom and dense top layers provide surface hardness and flexural strength to the board. Protein foaming agent is introduced into the lightweight core layer to create closed-cell structures. Combined with the physical lightweight properties of expanded perlite and hollow glass microspheres, this reduces the overall bulk density of the composite fireproof board, blocks heat transfer paths, and achieves a balance between lightweight design and fireproof insulation performance.

[0071] 2. This invention utilizes vacuum negative pressure to generate directional suction force, forcibly removing excess free water from the interior of the initially formed composite board that did not participate in the initial hydration reaction. Eliminating free water cuts off the path for capillary pore formation caused by natural evaporation of water later on, reducing matrix porosity and increasing density. Simultaneously, it eliminates the driving force for soluble salts to migrate and precipitate onto the surface of the composite fireproof board with water, preventing frost and efflorescence, and improving the overall dimensional stability of the board.

[0072] 3. The dense layer slurry and lightweight core layer slurry of this invention adopt a magnesium oxysulfate system. Lightly calcined magnesium oxide and magnesium sulfate heptahydrate hydrate in water to form a needle-like crystalline network that constitutes the load-bearing main phase. The magnesium oxysulfate modifier added to the formula can inhibit the formation of by-products and promote the hydration reaction towards the formation of a stable crystalline phase. Combined with the addition of polypropylene fibers of different lengths, a three-dimensional distribution structure is formed inside the slurry, resisting the shrinkage stress of the board and preventing micropore cracking. The pore-filling effect of wollastonite powder and the flexible bonding effect of latex powder after film formation enhance the toughness and crack resistance of the composite fireproof board. Attached Figure Description

[0073] Figure 1 This is an X-ray diffraction pattern of the matrix material prepared according to an embodiment of the present invention;

[0074] Figure 2 These are the Fourier transform infrared spectra of the embodiment of the present invention and the reference substrate material;

[0075] Figure 3 These are three-point bending load deflection curves of the test objects in the embodiments of the present invention and the comparative test objects;

[0076] Figure 4 These are tensile displacement-tensile stress curves of the test objects in the embodiments and comparative examples of the present invention;

[0077] Figure 5 This is a graph showing the airborne sound insulation frequency response characteristics of the test objects in the embodiments of the present invention and the comparative examples;

[0078] Figure 6 This is a graph showing the heat release rate of the test objects in the embodiments and comparative examples of the present invention. Detailed Implementation

[0079] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0080] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0081] Lightly calcined magnesium oxide is a conventional inorganic compound with the chemical formula MgO and CAS number 1309-48-4. It appears as a white powder and is insoluble in water.

[0082] Magnesium sulfate heptahydrate is a common inorganic salt compound with the chemical formula MgSO4·7H2O and CAS number 10034-99-8. It appears as colorless needle-like or oblique columnar crystals and is easily soluble in water.

[0083] Water is a common polar inorganic solvent with the chemical formula H2O and CAS number 7732-18-5.

[0084] Wollastonite powder uses a conventional commercially available product with a fineness of 800 mesh. It is a white powder and is a chain-like silicate inorganic mineral.

[0085] The latex powder used is a commercially available redispersible latex powder, which is a conventional polymer material and appears as a white, free-flowing powder. Using a commercially available product will not result in insufficient disclosure.

[0086] The pigments used are commercially available inorganic or organic pigments in the art. Their specific composition does not have a substantial impact on the chemical reaction system of the present invention and will not be described in detail.

[0087] Polypropylene fiber is a conventional high-molecular synthetic fiber. Its main component is isotactic polypropylene homopolymer, with CAS number 9003-07-0. It has a linear structure, and its chemical structure and physical properties can be confirmed through conventional commercial channels.

[0088] The magnesium oxysulfate modifier uses a commercially available, conventional composite phosphate magnesium oxysulfate modifier to improve the hydration and crystallization process of the magnesium oxysulfate system. Commercially available products can be used directly to meet the implementation requirements, and no further details are provided.

[0089] Protein foaming agents are commercially available hydrolyzed animal or plant proteins and are common building foaming additives.

[0090] The plant fiber is made from wood or bamboo powder with a fineness of 80-120 mesh, obtained from commercial channels, and is in a physical mixed state, which does not trigger any unknown chemical reactions.

[0091] Expanded perlite is a porous, lightweight inorganic silicate insulation material with a particle size of 0.5-1.5 mm and an internal honeycomb structure.

[0092] Hollow glass microspheres are thin-walled, closed-cell microspheres with a true density of 0.15-0.25 g / cm³.

[0093] The fiberglass mesh fabric is a commercially available mesh fabric woven from medium-alkali or alkali-free fiberglass yarn and coated with an alkali-resistant polymer emulsion.

[0094] UV paint uses commercially available light-curing coatings, mainly containing oligomers and photoinitiators, and its routine application does not lead to insufficient disclosure.

[0095] Preparation Examples 1-3:

[0096] Preparation Example 1:

[0097] This preparation example provides a method for preparing a dense layer slurry and a lightweight core layer slurry, including the following steps:

[0098] Step 1: Add 100 parts by weight of lightly calcined magnesium oxide, 55 parts by weight of magnesium sulfate heptahydrate, and 60 parts by weight of water to a mixer and stir at low speed for 4 minutes to obtain the first mixture.

[0099] Step 2: Add 35 parts by weight of 800-mesh wollastonite powder, 8 parts by weight of redispersible latex powder, and 3 parts by weight of pigment to the first mixture and stir at medium speed for 6 minutes to obtain the second mixture.

[0100] Step 3: Add 0.5 parts by weight of 6mm long polypropylene fiber and 2 parts by weight of magnesium oxysulfate modifier to the second mixture and stir at high speed for 3 minutes to obtain a dense slurry.

[0101] Step 4: Dilute the protein foaming agent with water 40 times, and then use a foaming machine to foam the diluted protein foaming agent to obtain protein foaming agent foam.

[0102] Step 5: Add 100 parts by weight of lightly calcined magnesium oxide, 65 parts by weight of magnesium sulfate heptahydrate, 75 parts by weight of water, and 2.5 parts by weight of magnesium sulfate modifier to a mixer and stir at low speed for 3 minutes to obtain the third mixture.

[0103] Step Six: Combine 28 parts by weight of wood flour with a fineness of 100 mesh, 20 parts by weight of expanded perlite with a particle size of 1.0 mm, and 10 parts by weight of material with a true density of 0.20 g / cm³. 3 Hollow glass microspheres and 0.2 parts by weight of polypropylene fibers with a length of 3 mm were added to the third mixture and stirred at medium speed for 5 minutes to obtain the matrix slurry.

[0104] Step 7: Add 6 volumes of protein foaming agent to the matrix slurry and stir slowly at 50 rpm for 3 minutes to obtain a lightweight core layer slurry.

[0105] Preparation Example 2:

[0106] This preparation example provides a method for preparing a dense layer slurry and a lightweight core layer slurry, including the following steps:

[0107] Step 1: Add 100 parts by weight of lightly calcined magnesium oxide, 65 parts by weight of magnesium sulfate heptahydrate, and 70 parts by weight of water to a mixer and stir at low speed for 5 minutes to obtain the first mixture.

[0108] Step 2: Add 50 parts by weight of 800-mesh wollastonite powder, 12 parts by weight of redispersible latex powder, and 5 parts by weight of pigment to the first mixture and stir at medium speed for 8 minutes to obtain the second mixture.

[0109] Step 3: Add 0.8 parts by weight of 6mm long polypropylene fiber and 3 parts by weight of magnesium oxysulfate modifier to the second mixture and stir at high speed for 3 minutes to obtain a dense slurry.

[0110] Step 4: Dilute the protein foaming agent with water 50 times, and then use a foaming machine to foam the diluted protein foaming agent to obtain protein foaming agent foam.

[0111] Step 5: Add 100 parts by weight of lightly calcined magnesium oxide, 80 parts by weight of magnesium sulfate heptahydrate, 90 parts by weight of water, and 3.5 parts by weight of magnesium sulfate modifier to a mixer and stir at low speed for 3 minutes to obtain the third mixture.

[0112] Step Six: Combine 40 parts by weight of bamboo powder with a fineness of 80 mesh, 30 parts by weight of expanded perlite with a particle size of 0.5 mm, and 15 parts by weight of material with a true density of 0.15 g / cm³. 3 Hollow glass microspheres and 0.4 parts by weight of polypropylene fibers with a length of 3 mm were added to the third mixture and stirred at medium speed for 5 minutes to obtain the matrix slurry.

[0113] Step 7: Add 10 volumes of protein foaming agent to the matrix slurry and stir slowly at 60 rpm for 3 minutes to obtain a lightweight core layer slurry.

[0114] Preparation Example 3:

[0115] This preparation example provides a method for preparing a dense layer slurry and a lightweight core layer slurry, including the following steps:

[0116] Step 1: Add 100 parts by weight of lightly calcined magnesium oxide, 45 parts by weight of magnesium sulfate heptahydrate, and 50 parts by weight of water to a mixer and stir at low speed for 3 minutes to obtain the first mixture.

[0117] Step 2: Add 20 parts by weight of 800-mesh wollastonite powder, 5 parts by weight of redispersible latex powder, and 1 part by weight of pigment to the first mixture and stir at medium speed for 5 minutes to obtain the second mixture.

[0118] Step 3: Add 0.3 parts by weight of 6mm long polypropylene fiber and 1 part by weight of magnesium oxysulfate modifier to the second mixture and stir at high speed for 3 minutes to obtain a dense slurry.

[0119] Step 4: Dilute the protein foaming agent with water 30 times, and then use a foaming machine to foam the diluted protein foaming agent to obtain protein foaming agent foam.

[0120] Step 5: Add 100 parts by weight of lightly calcined magnesium oxide, 50 parts by weight of magnesium sulfate heptahydrate, 60 parts by weight of water, and 1.5 parts by weight of magnesium sulfate modifier to a mixer and stir at low speed for 3 minutes to obtain the third mixture.

[0121] Step Six: Combine 15 parts by weight of wood flour with a fineness of 120 mesh, 10 parts by weight of expanded perlite with a particle size of 1.5 mm, and 5 parts by weight of material with a true density of 0.25 g / cm³. 3 Hollow glass microspheres and 0.1 parts by weight of polypropylene fibers with a length of 3 mm were added to the third mixture and stirred at medium speed for 5 minutes to obtain the matrix slurry.

[0122] Step 7: Add 3 volumes of protein foaming agent to the matrix slurry and stir slowly at 40 rpm for 2 minutes to obtain a lightweight core layer slurry.

[0123] Examples 1-3:

[0124] Example 1:

[0125] This embodiment provides a method for preparing a lightweight, high-strength magnesium oxysulfate composite fireproof board, including the following steps:

[0126] Step 1: Lay the first layer of fiberglass mesh at the bottom of the molding mold, pour the dense layer slurry prepared in Example 1 onto the surface of the first layer of fiberglass mesh, control the thickness of the dense layer slurry to be 3mm, scrape the dense layer slurry, let it stand for 18 minutes until it initially sets, and obtain the dense bottom layer.

[0127] Step 2: Lay a second layer of fiberglass mesh on the surface of the dense base layer, and pour the lightweight core layer slurry prepared in Example 1 onto the surface of the second layer of fiberglass mesh. Control the thickness of the lightweight core layer slurry to be 68% of the total thickness of the lightweight high-strength sulfur-oxygen magnesium composite fireproof board. Scrape the lightweight core layer slurry flat and let it stand for 35 minutes until it initially sets to obtain the lightweight core layer.

[0128] Step 3: Lay a third layer of fiberglass mesh on the surface of the lightweight core layer, pour the dense layer slurry prepared in Example 1 onto the surface of the third layer of fiberglass mesh, control the thickness of the dense layer slurry to be 3 mm, scrape the dense layer slurry smooth, and obtain the preliminary shaped composite board.

[0129] Step 4: Place the pre-formed composite board along with the forming mold into a vacuum suction filter and dehydrate it under negative pressure for 4 minutes using a vacuum degree of -0.07MPa to remove free water, thereby reducing the moisture content of the pre-formed composite board to 45% and obtaining a dehydrated composite board.

[0130] Step 5: Demold the dehydrated composite board, and then place the dehydrated composite board into a pre-curing room with a temperature of 35℃ and a humidity of ≥90% for 24 hours. Then transfer it to a normal temperature curing area with a temperature of 25℃ for 14 days to obtain the cured composite board.

[0131] Step 6: Sand the surface of the curing composite board to a fixed thickness, controlling the thickness tolerance to ±0.3mm. Clean the surface of the curing composite board and apply UV paint to the surface of the curing composite board to obtain a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board.

[0132] Example 2:

[0133] This embodiment provides a method for preparing a lightweight, high-strength magnesium oxysulfate composite fireproof board, including the following steps:

[0134] Step 1: Lay the first layer of fiberglass mesh at the bottom of the molding mold, pour the dense layer slurry prepared in Example 2 onto the surface of the first layer of fiberglass mesh, control the thickness of the dense layer slurry to be 4 mm, scrape the dense layer slurry flat, and let it stand for 20 minutes until it initially sets to obtain a dense bottom layer.

[0135] Step 2: Lay a second layer of fiberglass mesh on the surface of the dense base layer, and pour the lightweight core layer slurry prepared in Example 2 onto the surface of the second layer of fiberglass mesh. Control the thickness of the lightweight core layer slurry to be 75% of the total thickness of the lightweight high-strength sulfur-oxygen magnesium composite fireproof board. Scrape the lightweight core layer slurry flat and let it stand for 40 minutes until it initially sets to obtain the lightweight core layer.

[0136] Step 3: Lay a third layer of fiberglass mesh on the surface of the lightweight core layer, pour the dense layer slurry prepared in Example 2 onto the surface of the third layer of fiberglass mesh, control the thickness of the dense layer slurry to be 4 mm, scrape the dense layer slurry smooth, and obtain the preliminary shaped composite board.

[0137] Step 4: Place the pre-formed composite board along with the forming mold into a vacuum suction filter and dehydrate it under negative pressure for 5 minutes using a vacuum degree of -0.08MPa to remove free water, thereby reducing the moisture content of the pre-formed composite board to 40% and obtaining a dehydrated composite board.

[0138] Step 5: Demold the dehydrated composite board, and then place the dehydrated composite board into a pre-curing room with a temperature of 40℃ and a humidity of ≥90% for 24 hours. Then transfer it to a normal temperature curing area with a temperature of 30℃ for 14 days to obtain the cured composite board.

[0139] Step 6: Sand the surface of the curing composite board to a fixed thickness, controlling the thickness tolerance to ±0.3mm. Clean the surface of the curing composite board and apply a decorative finish to the surface of the curing composite board to obtain a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board.

[0140] Example 3:

[0141] This embodiment provides a method for preparing a lightweight, high-strength magnesium oxysulfate composite fireproof board, including the following steps:

[0142] Step 1: Lay the first layer of fiberglass mesh at the bottom of the molding mold, pour the dense layer slurry prepared in Example 3 onto the surface of the first layer of fiberglass mesh, control the thickness of the dense layer slurry to be 2 mm, scrape the dense layer slurry flat, let it stand for 15 minutes until it initially sets, and obtain the dense bottom layer.

[0143] Step 2: Lay a second layer of fiberglass mesh on the surface of the dense base layer, and pour the lightweight core layer slurry prepared in Example 3 onto the surface of the second layer of fiberglass mesh. Control the thickness of the lightweight core layer slurry to be 60% of the total thickness of the lightweight high-strength sulfur-oxygen magnesium composite fireproof board. Scrape the lightweight core layer slurry flat and let it stand for 30 minutes until it initially sets to obtain the lightweight core layer.

[0144] Step 3: Lay a third layer of fiberglass mesh on the surface of the lightweight core layer, pour the dense layer slurry prepared in Example 3 onto the surface of the third layer of fiberglass mesh, control the thickness of the dense layer slurry to be 2 mm, scrape the dense layer slurry smooth, and obtain the preliminary shaped composite board.

[0145] Step 4: Place the pre-formed composite board along with the forming mold into a vacuum suction filter and dehydrate it under negative pressure for 3 minutes using a vacuum degree of -0.06MPa to remove free water, thereby reducing the moisture content of the pre-formed composite board to 50% and obtaining a dehydrated composite board.

[0146] Step 5: Demold the dehydrated composite board, and then place the dehydrated composite board into a pre-curing room with a temperature of 30℃ and a humidity of ≥90% for 24 hours. Then transfer it to a normal temperature curing area with a temperature of 20℃ for 14 days to obtain the cured composite board.

[0147] Step 6: Sand the surface of the curing composite board to a fixed thickness, controlling the thickness tolerance to ±0.3mm. Clean the surface of the curing composite board and apply UV paint to the surface of the curing composite board to obtain a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board.

[0148] Comparative Examples 1-5:

[0149] Comparative Example 1:

[0150] Compared with Example 1, the difference is that the vacuum negative pressure dehydration treatment step is omitted, and the pre-formed composite board, together with the forming mold, is directly put into the pre-curing chamber for curing. All other aspects are the same.

[0151] Comparative Example 2:

[0152] Compared with Example 1, the difference is that expanded perlite and hollow glass microspheres are removed from the lightweight core layer formulation, and the amount of protein foaming agent foam added is increased by the same volume to make up for the volume loss caused by the removal of expanded perlite and hollow glass microspheres. All other aspects are the same.

[0153] Comparative Example 3:

[0154] Compared with Example 1, the difference is that layered paving and step-by-step initial setting are not performed. All the raw materials of the dense bottom layer, dense top layer and lightweight core layer are mixed into a single mixed slurry, which is then cast into a mold in one go. A layer of fiberglass mesh is laid on the upper and lower surfaces, and the rest is the same.

[0155] Comparative Example 4:

[0156] Compared with Example 1, the difference is that the step-by-step initial setting time is not controlled. After pouring the dense base layer and smoothing it, the second layer of fiberglass mesh is laid immediately and the lightweight core layer slurry is poured. Then, the third layer of fiberglass mesh is laid immediately and the surface dense layer slurry is poured to achieve continuous laying. All other aspects are the same.

[0157] Comparative Example 5:

[0158] Compared to Example 1, the difference lies in the absence of lightweight porous aggregates and foaming systems. Instead, the expanded perlite, hollow glass microspheres, and protein foaming agent in the lightweight core layer slurry are replaced with an equal volume of heavy talc filler. All other aspects remain the same.

[0159] Test Examples 1-6:

[0160] Test Example 1:

[0161] A 10cm × 10cm sample was taken from the central area of ​​the lightweight high-strength sulfur-oxygen magnesium composite fireproof board prepared in Examples 1, 2 and 3. The dense bottom layer material was separated from the lightweight core layer, and the dense bottom layer material was collected as the test object.

[0162] The collected test objects were placed in an agate mortar and ground into powder, which was then passed through a 200-mesh standard sieve to collect fine powder samples.

[0163] Spread the fine powder sample evenly in a petri dish, place it in a vacuum drying oven, set the temperature to 40℃, and dry continuously under vacuum for 24 hours until the sample reaches constant weight.

[0164] After constant weight, the fine powder sample is placed into the groove of the glass sample holder, the surface is flattened with a glass slide, and then placed in the test chamber of the X-ray diffractometer.

[0165] Set the operating parameters of the X-ray diffractometer, using Cu target Kα radiation, tube voltage set to 40kV, tube current set to 40mA, scanning range 2θ set to 5° to 70°, scanning step size controlled at 0.02°, and scanning rate controlled at 4° / min.

[0166] The equipment is started to scan and collect X-ray diffraction data to obtain the position and angle of the diffraction peaks and the corresponding relative intensity parameters.

[0167] Table 1. Data of main characteristic peak parameters of matrix materials in each embodiment via X-ray diffraction.

[0168] Test object Diffraction angle 2θ (°) Crystal phase determination and analysis Absolute values ​​of diffraction peak intensities (Counts) Example 1 11.81 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 2314.5 18.57 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 1892.1 33.42 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 985.6 42.85 MgO 412.3 62.29 MgO 287.9 Example 2 11.79 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 2439.7 18.62 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 1965.3 33.38 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 1024.2 42.91 MgO 358.6 62.33 MgO 245.4 Example 3 11.83 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 2153.2 18.55 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 1746.8 33.44 5Mg(OH) 2 ·MgSO 4 ·7H 2 O 911.4 42.82 MgO 563.1 62.26 MgO 321.5

[0169] See attached document Figure 1 , attached Figure 1 The horizontal axis represents the diffraction angle 2θ (°), and the vertical axis represents the diffraction intensity (au). In the figure, the solid colored line represents the test data of Example 1, the dark gray dashed line represents the test data of Example 2, and the gray dotted line represents the test data of Example 3.

[0170] The test results are as follows:

[0171] Based on the data in Table 1 and Figure 1 As can be seen from the X-ray diffraction patterns of Examples 1, 2, and 3, prominent diffraction peaks were detected near the 2θ angles of 11.8°, 18.6°, and 33.4°. Checking the standard card data confirmed that the positions of these characteristic peaks coincided with the diffraction positions of the 5Mg(OH)₂·MgSO₄·7H₂O crystalline phase. The 5Mg(OH)₂·MgSO₄·7H₂O crystalline phase is the core hydration product produced by the reaction of lightly calcined magnesium oxide and magnesium sulfate heptahydrate under conditions involving moisture. It forms a cross-linked needle-like crystalline network within the material matrix, providing basic support strength for the plate.

[0172] Unreacted magnesium oxide residual diffraction peaks were detected at 2θ angles of 42.9° and 62.3°. Combined with specific test numerical analysis, it can be seen that the diffraction intensity of the magnesium oxide residual peaks is lower than that of the 5Mg(OH)2·MgSO4·7H2O crystal phase.

[0173] Comparing the data differences between Examples 1, 2, and 3, it can be seen that when the process parameters are adjusted within the preset ratio and time span, the positions of the characteristic diffraction peaks do not shift, only exhibiting normal fluctuations in the absolute value of the diffraction intensity. The reactants underwent chemical transformation in the predetermined direction, generating the target crystalline phase, thus confirming that the preset formulation ratio and preparation process are practically operable and have a basis for material synthesis.

[0174] Test Example 2:

[0175] A sample of the lightweight, high-strength magnesium oxysulfate composite fireproof board prepared in Example 1 was taken, and the dense underlayer was separated and collected as a test sample. Following the formulation and steps described in Example 1, the magnesium oxysulfate modifier was removed from the components to prepare a reference underlayer material for use as a control.

[0176] The test sample and the reference substrate were placed in a vacuum drying oven and dried continuously at 45°C for 24 hours to remove surface adsorbed moisture.

[0177] Weigh 2 mg of the dried test sample and 200 mg of spectrally pure potassium bromide powder. Mix the test sample and potassium bromide powder in an agate mortar and grind clockwise for 5 minutes until the powder is evenly distributed. Perform the same procedure on the mixture of the reference substrate material and potassium bromide powder.

[0178] The ground and mixed powder is evenly spread into the tableting mold, and a pressure of 12 MPa is applied on the tablet press and held for 2 minutes to press the powder into a transparent circular sheet. The circular sheet is fixed on the sample cell support of the Fourier transform infrared spectrometer and the test chamber is sealed.

[0179] Set the operating parameters of the Fourier transform infrared spectrometer, and set the spectral scanning range to 4000 cm⁻¹. -1 Up to 400cm -1 Set the resolution to 4cm -1 The cumulative scan count is set to 32.

[0180] After starting the instrument and measuring the transmission background, the infrared absorption signal of the circular thin film is collected, and the transmittance value corresponding to each wavenumber point is recorded.

[0181] Table 2. Transmittance data of dense substrate material and reference substrate material in characteristic wavenumber bands.

[0182] Test object Wavenumber (cm⁻¹) Functional group vibration attribution determination Transmittance (%) Reference base material 3682.4 OH stretching vibration 41.2 3395.1 The stretching vibration of OH groups in water of crystallization 28.7 1632.8 Water of crystallization (HOH) bending vibration 65.4 1121.6 <![CDATA[SO4 2- antisymmetric stretching vibration]]> 32.1 598.5 Mg-O vibration 55.3 Example 1 Test Sample 3679.8 OH stretching vibration 38.6 3388.3 The stretching vibration of OH groups in water of crystallization 25.1 1630.2 Water of crystallization HOH bending vibration 63.8 1104.9 SO₄²⁻ and PO₄³⁻ vibrate in overlap. 29.4 1045.2 PO stretching vibration 48.7 592.1 Mg-O vibration 52.8

[0183] See attached document Figure 2 , attached Figure 2 The horizontal axis represents the wave number (cm). -1 The vertical axis represents transmittance (%). The solid black line in the figure represents the test data of the test sample in Example 1, and the dark gray dashed line represents the test data of the reference substrate material.

[0184] The test results are as follows:

[0185] Based on the data in Table 2 and Figure 2 From the table, we can see that OH represents oxygen-hydrogen bonds, Mg-O represents magnesium-oxygen bonds, and HOH represents the hydrogen-oxygen-hydrogen structure in water molecules. The absorption bands near 3680 cm⁻¹ and 3390 cm⁻¹ correspond to the stretching vibrations of the free hydroxide ions (OH bonds) in magnesium hydroxide and the stretching vibrations of the hydroxyl groups (OH bonds) in the crystal water of the magnesium oxysulfate hydration product phase, respectively.

[0186] In the infrared spectrum of the reference substrate material without the addition of magnesium oxysulfate modifier, 1121.6 cm⁻¹ -1 The position is attributed to the characteristic absorption peak of the asymmetric stretching vibration of the sulfate ion.

[0187] Comparing the spectral curves of the test sample in Example 1, the original characteristic absorption peak of sulfate shifted towards a lower wavenumber, moving to 1104.9 cm⁻¹. -1 At this location, the absorption band width increases to some extent. At 1045.2 cm⁻¹ -1 A new absorption band was detected, and based on the amount of composite phosphate added, the new absorption band was generated by the stretching vibration of the phosphorus-oxygen bond in the phosphate group. The shift in the characteristic peak position and the appearance of the new vibration signal indicate that the composite phosphate magnesium sulfate modifier participated in the bonding reaction after being mixed into the slurry.

[0188] Phosphate ions replace some water molecules and directly coordinate with magnesium ions to form magnesium oxyphosphate cross-links. This chemical coordination bonding process alters the original magnesium oxysulfate crystallization pathway, reduces the probability of lattice defects, and blocks the channels for water to penetrate into the interlayer of the lattice, thereby improving the matrix material's resistance to water erosion and maintaining the stability of the lightweight, high-strength magnesium oxysulfate composite fireproof board structure.

[0189] Test Example 3:

[0190] The plates prepared according to Examples 1, 2, 3, 2, 3, and 5 were used as test subjects.

[0191] Rectangular specimens with dimensions of 250 mm in length and 50 mm in width were cut along the longitudinal and transverse directions of the test object, respectively, retaining the original thickness of the plate after preparation and molding, and the edges of the rectangular specimens were polished to eliminate cutting burrs.

[0192] The rectangular sample was placed in a forced-air drying oven and baked at 60°C for 24 hours. It was then removed and placed in a desiccator to cool to 25°C.

[0193] Measure the dimensions of the rectangular sample in the length, width, and thickness directions using vernier calipers, and calculate the volume of the rectangular sample. Weigh the rectangular sample using an electronic balance, and calculate the apparent density by the ratio of the mass to the volume.

[0194] A rectangular specimen with its apparent density measured is placed on the test stand of a universal testing machine for a three-point bending test. The span between the two lower supports is set to 200 mm, and the upper pressure roller is adjusted to be directly above the center of the two lower supports.

[0195] Set the loading speed of the universal testing machine to 10 mm / min, and start the equipment to apply a continuous downward load to the center of the rectangular specimen.

[0196] The load values ​​and deflection values ​​at the center point of the rectangular specimen are collected in real time during the stress process using the software of the universal testing machine until the rectangular specimen fractures. The maximum failure load at fracture is recorded. The flexural strength is calculated based on the maximum failure load value, the span value, and the width and thickness of the rectangular specimen.

[0197] Table 3. Test data of apparent density and flexural strength of the plates in each embodiment and comparative example.

[0198] Test object Mass (g) Volume (cm³) Apparent density (g / cm3) Maximum breaking load (N) Flexural strength (MPa) Example 1 245.16 234.4 1.046 1133.8 19.35 Example 2 392.80 400.0 0.982 3092.5 18.12 Example 3 141.52 124.8 1.134 357.7 21.46 Comparative Example 2 251.02 234.4 1.071 737.1 12.58 Comparative Example 3 249.61 234.4 1.065 829.7 14.16 Comparative Example 5 431.48 234.4 1.841 949.8 16.21

[0199] See attached document Figure 3 , attached Figure 3 The horizontal axis represents deflection (mm), and the vertical axis represents load (N). In the figure, the solid black line represents the test data of Example 1, the gray dashed line represents the test data of Comparative Example 2, the dark gray dotted line represents the test data of Comparative Example 3, and the gray dotted line represents the test data of Comparative Example 5.

[0200] The test results are as follows:

[0201] Based on the data in Table 3 and Figure 3 From the content, it can be seen that in Comparative Example 5, when both the porous aggregate and the foaming material in the formula were replaced with talc powder, the apparent density of the board reached 1.841 g / cm³. 3 They are in a state of overweight, resulting in a high self-weight. The apparent density values ​​of Examples 1 to 3 are all around 0.98 g / cm³. 3 Up to 1.15 g / cm 3 Within the specified range, the goal of lightweight material design was achieved.

[0202] Comparative Example 2 eliminated expanded perlite and hollow glass microspheres, relying solely on increasing the amount of protein foaming agent for volume filling. Bending strength test data showed that the maximum destructive load of Comparative Example 2 was 737.1 N, and the bending strength was only 12.58 MPa. Combined with load-deflection curve analysis, the sample in Comparative Example 2 deformed and fractured under relatively low loads, exhibiting low load-bearing capacity. Hollow glass microspheres, as closed-cell microspheres, combined with porous expanded perlite to construct a honeycomb-like rigid framework within the matrix, distributing external loads. Without this rigid framework support, the thin-walled pores formed solely by gas encapsulation experienced stress concentration under pressure, leading to pore wall collapse and crack propagation, thus reducing bending performance.

[0203] Comparative Example 3 did not employ a layered casting method; instead, it prepared a homogeneous mixed slurry from all components. Bending strength data showed a bending strength of 14.16 MPa, lower than the 19.35 MPa of Example 1. In Example 1, by controlling the curing time, low-density porous material was concentrated in the core of the composite board, while high-density continuously cured phases were concentrated in the upper and lower surface layers, forming a symmetrically distributed gradient structure. Under three-point bending load conditions, the material cross-section was subjected to bending moment. The upper and lower edges of the material cross-section experienced the greatest tensile and compressive stresses, while the stress in the central region approached zero. The dense and rigid upper and lower surface layers of Example 1 could resist the ultimate tensile and compressive deformation generated at the bending edges, while the low-density core layer provided thickness support and transferred interlaminar shear force. The homogeneous structure of Comparative Example 3 randomly distributed low-strength foamed pores to the compressive and tensile edge regions, reducing the outer layer's resistance to deformation and thus weakening the overall bending failure limit of the board.

[0204] Test Example 4:

[0205] Square samples with dimensions of 50mm × 50mm were cut from the central area of ​​the plates prepared in Example 1, Comparative Example 1, and Comparative Example 4, respectively, and used as test objects for interlayer bonding performance. The upper and lower surfaces of the square samples were polished with fine sandpaper to remove surface dust and demolding residue.

[0206] A two-component high-strength structural adhesive composed of epoxy resin and curing agent was prepared, and the uniformly mixed high-strength structural adhesive was evenly applied to the upper and lower surfaces of a square sample.

[0207] Align the center of a 50mm×50mm aluminum alloy puller and attach it to the adhesive layer on the upper and lower surfaces of the square sample. Apply a constant pressure of 10N to the top of the aluminum alloy puller to maintain the compression state, and let it stand at room temperature for 48 hours to allow the structural adhesive to fully cure.

[0208] The square specimen with the aluminum alloy pull-out head bonded to it is loaded into the tensile fixture of the universal testing machine. The concentricity of the upper and lower fixtures is adjusted to prevent eccentric torque from occurring during the test.

[0209] Set the universal testing machine to normal tensile mode and set the tensile speed to 2 mm / min.

[0210] Start the testing machine to apply a normal tensile load perpendicular to the plate surface to the square specimen, and simultaneously record the tensile displacement data of the testing machine and the corresponding pull-out load value.

[0211] Observe the instantaneous location of the square specimen's fracture, record the layer where the fracture occurred, and calculate the vertical tensile strength value based on the maximum pull-out load value and the tensile cross-sectional area of ​​the square specimen.

[0212] Table 4. Test data of interlayer vertical tensile strength of the plates in each embodiment and comparative example.

[0213] Test object Maximum pull-out load (N) Vertical tensile strength (MPa) Observation of the fracture location of the sample Example 1 3182.4 1.273 Lightweight core layer internal fracture 3215.1 1.286 Lightweight core layer internal fracture Comparative Example 1 1714.8 0.685 Lightweight core fracture accompanied by interlaminar cracking 1689.5 0.675 The lightweight core layer has a loose and fractured internal structure. Comparative Example 4 1083.2 0.433 Delamination at the interface between the core layer and the sublayer 1045.9 0.418 The interface between the core layer and the bottom layer has separated.

[0214] See attached document Figure 4 , attached Figure 4 The horizontal axis represents tensile displacement (mm), and the vertical axis represents tensile stress (MPa). In the figure, the solid black line represents the test data of Example 1, the dark gray dashed line represents the test data of Comparative Example 1, and the gray dotted line represents the test data of Comparative Example 4.

[0215] The test results are as follows:

[0216] Based on the data in Table 4 and Figure 4 The results show that the test object in Comparative Example 4 fractured at a tensile displacement of 0.6 mm, with a vertical tensile strength of only 0.418 MPa to 0.433 MPa. The fracture occurred mainly at the interface between the lightweight core layer and the dense sublayer. The continuous casting process failed to provide a time buffer for the slurry's self-hydration reaction to establish the initial network skeleton, and the weight of the upper layer caused different slurries at the interface to mix and interfere with each other. This component mixing disrupted the continuity of the cementitious material's hydration and crystallization process at the interface, resulting in structural defects at the interface. Under normal tensile stress, the structural defects at the interface became stress concentration sources, leading to delamination.

[0217] The test object in Comparative Example 1 did not undergo a vacuum negative pressure dehydration process. Its vertical tensile strength fluctuated within the range of 0.68 MPa, and the fracture manifested as a loose internal structure with cracks. Free water was trapped between different layers, occupying the space volume for gel growth. During the subsequent evaporation and drying stage, the water escape process left behind a large number of interconnected pores and gaps, reducing the overall density of the board and weakening the material's ultimate load resistance to axial tensile stress.

[0218] In Example 1, the test object recorded a vertical tensile strength exceeding 1.27 MPa, and the fracture point shifted to the interior of the lightweight core layer. No separation occurred at the interface, indicating that the maximum stress that the interlayer bond could withstand exceeded the cohesive limit of the porous core material itself. After controlling the interface solidification state, vacuum negative pressure filtration removed excess free water, and the external negative pressure difference exerted a downward compressive effect on the formed layered structure. This compressive state caused the slurry pores at adjacent interfaces to move closer together and compress. Accompanied by the initiation of sulfur-oxygen-magnesium cementitious phase crystals during the curing stage, the crystallized products interpenetrated and cross-linked across the interface pores, forming an interlocking anchoring structure and increasing the threshold of the interlayer bond's resistance to external force separation.

[0219] Test Example 5:

[0220] The plates prepared by Example 1, Comparative Example 3, and Comparative Example 5 were cut into square test plates with a size of 1000mm×1000mm, and the cutting burrs on the edges of the test plates were removed using a grinder.

[0221] The test plate is vertically fixed inside the test window in the wall between the sound-emitting chamber and the receiving chamber of the acoustic testing laboratory, and the position of the test plate is adjusted to be flush with the wall surface.

[0222] Damping rubber strips are filled around the perimeter of the test plate, and silicone sealant is used to seal the seam between the test plate and the test window frame, blocking the path of sound waves diffracting through the gap.

[0223] An omnidirectional dodecahedral loudspeaker is installed in the sound-generating room, and a pink noise continuous sound source with a frequency range covering 100Hz to 3150Hz is set up for the loudspeaker.

[0224] The sound level was measured and recorded in the acoustic chamber using a sound level meter, representing the average spatial sound pressure level.

[0225] A multi-channel microphone array was deployed in the receiving room to collect the average sound pressure level of the space reaching the receiving room after transmission through the test plate. The background noise and reverberation time inside the receiving room were measured for data correction.

[0226] The sound pressure level difference between the transmitting and receiving chambers at each center frequency point is extracted. The sound absorption of the receiving chamber and the area parameters of the test plate are then used for correction calculations to obtain the airborne sound insulation at each frequency point. The weighted sound insulation of the test plate is then calculated with reference to the standard curve.

[0227] Table 5. Test data of airborne sound insulation of the boards in each embodiment and comparative example.

[0228] Test object 125Hz sound insulation (dB) 250Hz sound insulation (dB) 500Hz sound insulation (dB) Sound insulation at 1000Hz (dB) Sound insulation at 2000Hz (dB) Sound insulation at 3150Hz (dB) Weighted sound insulation Rw (dB) Example 1 29.4 36.2 42.8 48.5 52.1 55.6 45.3 28.9 35.8 43.1 47.9 51.7 56.2 44.8 Comparative Example 3 22.1 26.5 31.2 34.7 37.8 40.4 32.5 21.6 27.2 30.8 33.9 38.3 39.8 31.9 Comparative Example 5 32.5 37.1 41.5 38.2 40.6 46.2 39.7

[0229] See attached document Figure 5 , attached Figure 5 The horizontal axis represents the center frequency (Hz), and the vertical axis represents the sound insulation (dB). In the figure, the solid black line represents the test data of Example 1, the gray dotted line represents the test data of Comparative Example 3, and the dark gray dashed line represents the test data of Comparative Example 5.

[0230] The test results are as follows:

[0231] Based on the data in Table 5 and Figure 5The contents show that the material composition of the board in Comparative Example 5 is a solid, heavy filler, and the overall structure is a single, dense state. When sound waves come into contact with the dense material in the low-frequency region, they are reflected under the control of the mass law. As the frequency rises to the 800Hz to 1250Hz range, the incident sound wave frequency is close to the natural bending vibration frequency of the single-thickness material, exciting the coincidence effect. The sound wave energy radiates to the back surface through material resonance, causing a nonlinear drop in the high-frequency sound insulation data.

[0232] Comparative Example 3 shows a board with a uniformly distributed lightweight foamed slurry structure. Test data confirms that the uniform, loose structure lacks a rigid boundary to block sound pressure penetration; after penetrating the front interface, sound waves continue to travel in a straight line within the homogeneous material. Due to the lack of an internal reflection and dissipation layer formed by the acoustic impedance span, the sound propagation resistance is limited, and the sound insulation capability remains at a low level.

[0233] Example 1: The board material is constructed with a sandwich structure consisting of a high-density surface layer, a low-density core layer, and a high-density bottom layer. When sound waves generated by an external sound field are projected onto the surface of the first dense layer, they encounter a hard interface, causing the initial energy to be attenuated by the rebound. Sound waves penetrating the first dense layer and entering the lightweight core layer undergo diffraction and friction when encountering the cavities of expanded perlite particles and the closed pore groups constructed from foamed proteins, resulting in the conversion of sound energy into heat energy and loss. Residual sound waves reaching the interface between the second dense layer and the lightweight core layer encounter an acoustic impedance mismatch caused by the density difference. This impedance difference forces the sound waves to bounce back to the lightweight core layer region from the inner boundary of the second dense layer, undergoing secondary energy dissipation. The combined effect of the acoustic impedance interface reflection mechanism and the porous energy dissipation mechanism increases the attenuation value of the sound source transmitted outward through the board material, blocking the continuous transmission of sound waves within the test frequency band.

[0234] Test Example 6:

[0235] The plates prepared by Example 1, Example 2 and Comparative Example 2 were cut into square samples with a size of 100mm×100mm respectively, and the thickness and initial mass of each square sample were recorded.

[0236] The bottom and four sides of the square sample were sealed with commercial aluminum foil, leaving only the top surface of the square fully exposed as the surface to receive heat radiation.

[0237] The wrapped square sample was placed in a constant temperature and humidity chamber set at 23°C and 50% relative humidity for 48 hours to allow the internal moisture content of the sample to reach equilibrium.

[0238] The preheating cone calorimeter was used to set the radiative heat flow parameter of the radiative cone to 50 kW / m². 2 Turn on the exhaust system and calibrate the oxygen and carbon dioxide analyzers.

[0239] Place the conditioned square sample horizontally on the weighing tray of the cone calorimeter, and adjust the distance between the bottom of the radiation cone and the exposed upper surface of the square sample to 25 mm.

[0240] Move the electronic igniter over the square sample, start the test program, and simultaneously begin recording the test time.

[0241] The combustion of a square sample after heating was continuously monitored using a data acquisition system. The duration of a sustained flame on the sample surface was recorded, and data on changes in gas concentration and mass loss during combustion were collected. These data were then used to calculate the heat release rate and total heat release. The test was stopped when the mass of the square sample ceased to change.

[0242] Table 6. Test data on the combustion performance of the plates in each embodiment and comparative example.

[0243] Test object Ignition time (s) Peak heat release rate (kW / m²) Total heat released (MJ / m²) Quality retention rate after testing (%) Example 1 Unignited 12.4 3.1 88.6 Comparative Example 2 Unignited 15.2 3.9 86.2 58 38.6 11.5 76.4

[0244] See attached document Figure 6 , attached Figure 6 The horizontal axis represents time (s), and the vertical axis represents the heat release rate (kW / m³). 2 In the figure, the dark gray dotted lines represent the test data of Example 1, the gray dashed lines represent the test data of Example 2, and the black solid lines represent the test data of Comparative Example 2.

[0245] The test results are as follows:

[0246] Based on the data in Table 6 and Figure 6 From the content, it can be seen that at 50kW / m 2 Under sustained intense thermal radiation, no continuous open flame combustion was observed on the sample surfaces of Examples 1 and 2 throughout the entire test period. The heat release rate curves remained within a low value range without a steep exothermic peak, and the mass retention rate after the test remained above 86%. The 5Mg(OH)₂·MgSO₄·7H₂O crystalline phase generated by the hydration of the magnesium oxysulfate cementitious material contains a large amount of water of crystallization. When the external temperature rises, the water of crystallization undergoes a dehydration reaction upon heating. This chemical process absorbs heat from the surrounding environment, slowing down the rate of temperature rise on the sample surface. The water vapor generated during dehydration escapes outward, reducing the concentration of flammable gases on the sample surface and blocking the oxidation reaction pathway that supports combustion.

[0247] In Comparative Example 2, the inorganic lightweight porous aggregate was removed from the formulation, and the amount of protein foaming agent added was increased by an equal volume. Test data showed that the Comparative Example 2 sample was ignited in 58 seconds, producing an open flame, and the peak heat release rate increased to 38.6 kW / m³. 2The mass retention rate decreased to 76.4% after the test. Increasing the amount of protein foaming agent increased the proportion of organic polymers inside the matrix. Organic matter undergoes pyrolysis under high-temperature radiation, producing combustible hydrocarbon gases and releasing heat, leading to an increase in the overall heat release and aggravated mass loss of the material.

[0248] Example 1 uses inorganic foamed expanded perlite and hollow glass microspheres to construct the spatial framework of a lightweight core layer. The inorganic aggregate possesses resistance to thermal shrinkage and non-combustible properties under high-temperature conditions. The glass microspheres melt upon heating to form a glassy glaze layer covering the matrix, while the expanded perlite particles participate in constructing a fire-resistant and heat-insulating barrier, preventing external heat flow from penetrating the interior of the board. The inorganic porous aggregate, combined with the magnesium oxysulfate hydration network, controls the total load of combustible organic matter in the substrate, meeting the A1 grade non-combustible performance requirements for building materials.

Claims

1. A lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board, characterized in that, It includes a first layer of fiberglass mesh, a dense bottom layer, a second layer of fiberglass mesh, a lightweight core layer, a third layer of fiberglass mesh, and a dense top layer, which are stacked sequentially from bottom to top; the dense bottom layer and the dense top layer are formed by curing a dense layer slurry, and the lightweight core layer is formed by curing a lightweight core layer slurry; The dense layer slurry is made from the following raw materials in parts by weight: Lightly calcined magnesium oxide: 100 parts; Magnesium sulfate heptahydrate: 45-65 parts; Water: 50-70 parts; Wollastonite powder: 20-50 parts; Latex powder: 5-12 parts; Pigment: 1-5 parts; Polypropylene fiber: 0.3-0.8 parts; Magnesium sulfide modifier: 1-3 parts; The lightweight core layer slurry is made by mixing a matrix slurry with a protein foaming agent, and 3-10 parts by volume of the protein foaming agent are added to the matrix slurry. The matrix slurry is made from the following raw materials in parts by weight: Lightly calcined magnesium oxide: 100 parts; Magnesium sulfate heptahydrate: 50-80 parts; Water: 60-90 parts; Plant fiber: 15-40 parts; Expanded perlite: 10-30 parts; Hollow glass microspheres: 5-15 parts; Polypropylene fiber: 0.1-0.4 parts; Magnesium sulfide modifier: 1.5-3.5 parts.

2. The lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board according to claim 1, characterized in that, The length of the polypropylene fibers in the dense layer slurry is 6 mm; the length of the polypropylene fibers in the matrix slurry is 3 mm.

3. The lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board according to claim 1, characterized in that, The thickness of the dense sublayer and the dense surface layer are both 2-4 mm; The thickness of the lightweight core layer accounts for 60%-75% of the total thickness of the lightweight high-strength sulfur-oxygen magnesium composite fireproof board.

4. The lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board according to claim 1, characterized in that, The wollastonite powder has a fineness of 800 mesh; the latex powder is a redispersible latex powder; the true density of the hollow glass microspheres is 0.15-0.25 g / cm³. 3 The plant fiber is wood flour or bamboo flour with a fineness of 80-120 mesh; the expanded perlite has a particle size of 0.5-1.5 mm.

5. A method for preparing a lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board according to any one of claims 1-4, characterized in that, Includes the following steps: A first layer of fiberglass mesh is laid at the bottom of the molding mold, and the dense layer slurry is poured onto the surface of the first layer of fiberglass mesh. The dense layer slurry is then smoothed and allowed to stand until it initially sets to obtain the dense bottom layer. A second layer of fiberglass mesh is laid on the surface of the dense base layer, and the lightweight core layer slurry is poured onto the surface of the second layer of fiberglass mesh. The lightweight core layer slurry is then leveled and allowed to stand until initial setting to obtain the lightweight core layer. A third layer of fiberglass mesh is laid on the surface of the lightweight core layer, and the dense layer slurry is poured onto the surface of the third layer of fiberglass mesh. The dense layer slurry is then smoothed to obtain the dense surface layer, thereby obtaining a preliminary shaped composite board. The pre-formed composite board, together with the forming mold, is placed in a vacuum suction filter device for negative pressure dehydration treatment to remove free water and obtain a dehydrated composite board. Demolding of the dehydrated composite board, sending the demolded dehydrated composite board into a pre-curing room for curing, and then transferring it to a room temperature curing area for curing, to obtain a cured composite board. The surface of the curing composite board is sanded to a fixed thickness to clean it. Then, UV paint or decorative coating is applied to the surface of the curing composite board to obtain the lightweight, high-strength sulfur-oxygen-magnesium composite fireproof board.

6. The preparation method according to claim 5, characterized in that, The dense layer slurry is prepared in advance through the following steps: Add the prescribed amounts of lightly calcined magnesium oxide, magnesium sulfate heptahydrate, and water to a mixer and stir at low speed for 3-5 minutes to obtain the first mixture. Add the formulated amounts of wollastonite powder, latex powder, and pigment to the first mixture and stir at medium speed for 5-8 minutes to obtain the second mixture. The formulated amounts of polypropylene fiber and magnesium oxysulfate modifier are added to the second mixture and stirred at high speed for 3 minutes to obtain the dense slurry.

7. The preparation method according to claim 5, characterized in that, The lightweight core layer slurry is prepared in advance through the following steps: Water is added to the protein foaming agent to dilute it 30-50 times, and the diluted protein foaming agent is foamed through a foaming machine to obtain the protein foaming agent foam. Add the formulated amounts of lightly calcined magnesium oxide, magnesium sulfate heptahydrate, water, and magnesium sulfate modifier to a mixer and stir at low speed for 3 minutes to obtain the third mixture. The plant fiber, expanded perlite, hollow glass microspheres and polypropylene fiber in the formula amount are added to the third mixture and stirred at medium speed for 5 minutes to obtain the matrix slurry. Add the protein foaming agent foam of the formulation volume fraction to the matrix slurry, and stir slowly at 40-60 rpm for 2-3 minutes to obtain the lightweight core layer slurry.

8. The preparation method according to claim 5, characterized in that, The vacuum degree of the negative pressure dehydration process is -0.06MPa to -0.08MPa, and the dehydration time is 3-5 minutes. After removing the free water, the moisture content of the pre-formed composite board is reduced to 40%-50%.

9. The preparation method according to claim 5, characterized in that, The temperature of the pre-curing chamber is 30-40℃, the humidity is greater than or equal to 90%, and the curing time is 24 hours; The temperature in the ambient temperature curing area is 20-30℃, and the curing time is 14 days.

10. The preparation method according to claim 5, characterized in that, Scrape the dense slurry layer smooth and let it stand until initial setting time is 15-20 minutes; The lightweight core layer slurry is scraped smooth and allowed to stand until initial setting in 30-40 minutes; the thickness tolerance of the fixed-thickness sanding is controlled at ±0.3mm.